Paintable room-temperature phosphorescent liquid formulations of alkylated bromonaphthalimide - Goudappagouda; Manthanath, A.; Wakchaure, V. C.; Ranjeesh, K. C.; Das, T.; Vanka, K.; Nakanishi, T.; Babu, S. S. (Angewandte Chemie - International Edition, 2019)
Organic phosphors have been widely explored with an understanding that crystalline molecular ordering is a requisite for enhanced intersystem crossing. In this context, we explored the room‐temperature phosphorescence features of a solvent‐free organic liquid phosphor in air. While alkyl chain substitution varied the physical states of the bromonaphthalimides, the phosphorescence remained unaltered for the solvent‐free liquid in air. As the first report, a solvent‐free liquid of a long swallow‐tailed bromonaphthalimide exhibits room‐temperature phosphorescence in air. Doping of the phosphor with carbonyl guests resulted in enhanced phosphorescence, and hence a large‐area paintable phosphorescent liquid composite with improved lifetime and quantum yield was developed.